THE IMPACT OF LONGER WORKING TO MERCURY LEVEL (HG) IN BLOOD OF THOSE TRADITIONAL GOLD MINERS AT DESA PANTON LUAS KABUPATEN ACEH SELATAN - Syafruddin Din (Universitas Muhammadiyah Sumatera Utara, 2019)
It is seen traditional gold mining workings where there use mercury to process out amalgamation has been done for more than 4 years already at Desa Panton Luas. This paper is to determine the impact of longer work with Mercury level existed in the blood of those mining workers with traditional gold miners on the location. This paper is descriptive research and found that the mercury level existed in blood for a working period of average a year noted 5.57 ppb, for 2 years average noted 6.52 ppb, in three years average 7.34 ppb, and for 4 years average noted 8.95 ppb. As has been conducted in statistical test analysis indicated that there is a difference between a long-time off work in a year to 4 years serving with p < 0.05. Still, an existing difference of increasing mercury level in blood with a long time of one, two, three and four years serving in the field but it is threshold value as recommended by WHO namely 5-10 ppb. Keywords: mercury blood level, long duration of working, gold mining